Seismic Evaluation of Steel Plate Shear Walls in Different Configurations - Seyed Mohmmad Ali Abbaspoor Haghighat; Ali Alibazi; Reza Moradifard; Lotfi Guizani; Munzer Hassan (Journal of Rehabilitation in Civil Engineering)
Steel plate shear walls (SPSWs) are a cost-efficient system to resist seismic lateral loads. Post-buckling strength, tension field action, and high energy absorption capacity are among the advantages of SPSWs. A beam-coupled SPSW consists of two pairs of plates connected by the coupling beam. The steel plate of a beam-coupled SPSW is typically connected to horizontal and vertical boundary elements. The connection of the steel plate to the vertical boundary elements induces an axial load and a bending moment in the plate. This research addresses the lack of comprehensive evaluations of coupled SPSWs with varying coupling beam mechanisms, such as flexural-shear behavior. Nine numerical models with different configurations and coupling degrees are developed through plastic design. Numerical analyses are carried out in SAP2000, ABAQUS, and OpenSees. Pushover, cyclic, and nonlinear time-history analyses indicate that SHEAR is the optimal model. Nonlinear static and nonlinear time-history analyses are sometimes ineffective for seismic evaluation, and incremental dynamic analysis (IDA) using FEMA P-695 demonstrate that the FLEX model can be more optimal when the construction cost and ultimate performance limit (i.e., collapse prevention (CP) limit) are incorporated. However, INT would be the most optimal model at the life safety (LS) limit.Therefore, The study provides a robust framework for optimizing seismic performance across different building heights, contributing to safer and more economical structural designs.